Different facets of bacterial and fungal communities drive soil multifunctionality in grasslands spanning a 3500 km transect. (8th November 2022) - Ma, Linna; Zhang, Chaoxue; Xu, Xiaofeng; Wang, Congwen; Liu, Guofang; Liang, Cunzhu; Zuo, Xiaoan; Wang, Chengjie; Lv, Yixia; Wang, Renzhong
Abstract: Soil microbial communities are essential in regulating ecosystem functions and services. However, the importance of bacterial and fungal communities as predictors of multiple soil functions (i.e. soil multifunctionality) in grassland ecosystems has not been studied systematically. Here, we measured soil microbial diversity, community composition, biomass and multiple soil functions of 41 sites in five grassland ecosystems spanning a 3500 km northeast–southwest transect. The random forest algorithm was adopted to determine the importance of geographical location, climatic, altitude, edaphic, plant and microbial predictors in driving a proxy of soil multifunctionality (seven soil functions in this study). Moreover, structural equation models were employed to examine the direct and indirect effects of those predictors on soil multifunctionality. Our results demonstrated that soil multifunctionality was positively driven by soil fungal diversity but not by bacterial diversity. Fungal phylogenetic diversity (presence of different evolutionary lineages) showed stronger positive relationships with soil multifunctionality than taxonomic diversity (richness of species). Dominant bacterial taxa, particularly of phyla Actinobacteria and Proteobacteria, were positively associated with soil multifunctionality, while none of the fungal taxa were found to regulate soil multifunctionality. Furthermore, both fungal and bacterial biomass had significant effects on soil multifunctionality, while the effect of microbial biomass was weaker than that of fungal diversity and bacterial taxa. Importantly, the direct positive effects of soil fungal diversity, dominant bacterial taxa, and fungal and bacterial biomass were maintained after accounting for multiple predictors in grassland ecosystems. This study provided strong empirical evidence that soil multifunctionality was driven by different facets of the bacterial and fungal communities in the grassland ecosystems. Our results also highlighted that any loss of fungal diversity, dominant bacterial taxa and microbial biomass might reduce soil multifunctionality, exacerbating ecosystem functions and services such as soil fertility, primary production and climate mitigation in grassland ecosystems. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.